Gynecologic Oncology Research and Practice - Coleman, Robert; Monk, Bradley J.; Herzog, Thomas J.
Gynecologic Oncology Research and Practice is an open access, peer-reviewed journal that publishes articles on all cancers of the female reproductive system, including cervical cancer, ovarian cancer, uterine cancer, vaginal cancer, and vulvar cancer. The journal considers articles related to the pathophysiology, prevention, diagnosis, and treatment of these cancers. The journal aims to serve as an international platform for sharing laboratory and clinical findings by offering a high-visibility forum for new insights and discussions among scientists, physicians and oncologists.